The Effect of Halal Label on Consumer Purchasing Decisions with Religiosity as a Mediating Variable - Rahman, Muhammad Ubaidillah; Marsudi; Satiti, Novita Ratna (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to prove the effect of halal labels on consumer purchasing decisions with religiosity as a mediating variable for ice cream and tea of Mixue consumers in Malang City. A sample of 112 respondents used a non-probability sampling strategy with a purposive sampling technique. Data collection uses a questionnaire distributed to Mixed consumers. The analysis technique used in this study uses path analysis. It indicates halal labels can have a positive and significant effect on purchasing decisions. Halal labels can have a positive and significant effect on religiosity. Religiosity can have a positive and significant effect on purchasing decisions. However, religiosity cannot mediate between halal labels and purchasing decisions.